Cervical spondylotic myelopathy presenting as a “pancake enhancement” on MRI of the spinal cord: A case report and review of literature - Nava Raj Sharma; Bharosa Sharma; Saral Lamichhane; Madalasa Pokhrel; Prajwal Shrestha (Clinical Case Reports)
Abstract Spondylotic myelopathy involves chronic spinal cord compression from degenerative spine changes presenting a myriad of neurological and pain symptoms. We report a case of cervical myelopathy with transverse pancake‐like gadolinium enhancement seen on MRI in a 42‐year‐old gentleman with progressive bilateral upper extremity numbness, tingling, and impaired gait.